The Hallucinogenic Mushrooms: Diversity, Traditions, Use and Abuse with Special Reference to the Genus Psilocybe - GASTON GUZMAN HUERTA (Fungi from Different Environments, 2009)
The traditions, uses and abuses, and studies of hallucinogenic mushrooms, mostly species of Psilocybe, are reviewed and critically analyzed. Amanita muscaria seems to be the oldest hallucinogenic mushroom used by man, although the first hallucinogenic substance, LSD, was isolated from ergot, Claviceps purpurea, Amanita muscaria is still used in North Eastern Siberia and by some North American Indians. In the past, some Mexican Indians, as well as Guatemalan Indians possibly used A. muscaria. Psilocybe has more than 150 hallucinogenic species throughout the world, but they are used in traditional ways only in Mexico and New Guinea. Some evidence suggests that a primitive tribe in the Sahara used Psilocybe in religions ceremonies centuries before Christ. New ethnomycological observations in Mexico are also described.